A Study of Visual Graphical Analysis of Arab Women Support Institutions’ Awareness Posters - Barakat, Fadwa Hamdi; Alrabaai , Ehsan Ersan (Dirasat: Human and Social Sciences, 2023)
Objectives: This study compares formal, symbolic, and semantic features of contemporary posters from Arab Women Support Institutions. It analyzes visual elements for clarity and compatibility with Arab culture and institutional policies promoting the role of Arab women. Methods: A visual descriptive-analytical method has been used in this study to demonstrate content and events. Data was collected on women’s issues from documents, periodicals, prints, and electronic sources. Certain forms were designed to focus on the description of the visual elements, namely texture, pattern, color, value, and saturation in addition to the composition dimension to illustrate the relationships between the formal features of the posters and their implicit meaning. In addition, the study investigates the compatibility between the shape and the ideological content of the posters. Results: The descriptive analysis of the presented posters concluded that some visual indications are unclear, as their meanings cannot be deduced immediately, but they are symbols that require thinking and contemplation to extract perceptions. The study also found that there are discrepancies between the formal features in several images used in the awareness campaigns and the policies of the institutions and their theoretical legislation. Conclusions: This study analyzes the significance of image values in graphic design for public influence, proposing them as a criterion for assessing design features. It suggests that designers and researchers in graphic design concentrate on poster content to amplify the impact of women’s image in society and challenge public expectations through awareness deconstruction.